New Mediterranean Biodiversity Records (July, 2017) - GEROVASILEIOU, V.; AKEL, E.H.KH.; AKYOL, O.; ALONGI, G.; AZEVEDO, F.; BABALI, N.; BAKIU, R.; BARICHE, M.; BENNOUI, A.; CASTRIOTA, L.; CHINTIROGLOU, C.C.; CROCETTA, F.; et al. (Mediterranean Marine Science, 2017)
This Collective Article presents information on 37 taxa belonging to 6 Phyla and extending from the western Mediterranean to the Levantine Sea. The new records were found in 10 countries as follows: Algeria: first reports on the presence of the fish species Lesueurigobius sanzi, L. friesii, L. suerii and Luvarus imperiali; France: first record of the alien nudibranch Godiva quadricolor; Italy: first record of an adult-sized red emperor snapper Lutjanus sebae from the southern Tyrrhenian Sea; first record of the pantropical rhodophyte Chondria curvilineata and the Lessepsian fish Siganus luridus from southern Sicily; record of a large pregnant female Dusky shark Carcharhinus obscurus off Sicily; Albania: first record of the fish Ruvettus pretiosus, new records of the alien molluscs Conomurex persicus, Bursatella leachii, Dendostrea cf. folium, Fulvia fragilis and Ruditapes philippinarum and additional report of the alien bivalve Pinctada imbricata radiata; Montenegro: first record of the sea slug Thecacera pennigera in the Adriatic Sea; Greece: first record of the invasive calcarean sponge Paraleucilla magna in Greek waters; occupancy estimation of the established cryptogenic rhodophyte Ganonema farinosum, the alien crustacean Percnon gibbesi and the alien fish species Fistularia commersonii, Siganus luridus, and S. rivulatus along the Cretan coastline; first record of the alien mollusc Sticteulima lentiginosa in Greek waters suggesting a westward unintentional expansion of this species; Turkey: photographic evidence of interactions of the monk seal Monachus monachus with sea-cage farms in the Turkish Aegean Sea and first record of the yellow boxfish Ostracion cubicus in the Turkish Mediterranean; Cyprus: first records of the rare speleophilic fish Thorogobius ephippiatus and Grammonus ater in Cyprus, extending the known distribution of the latter Mediterranean endemic species eastwards; first records of the alien fish Kyphosus vaigiensis and the alien crustacean species Macrophthalmus indicus and Carupa tenuipes as well as additional records of the alien echinoderm Diadema setosum and the alien ascidian Symplegma brakenhielmi in the country; Lebanon: first report on the presence of the four alien fish species Cephalopholis taeniops, Equulites popei, Pseudupeneus prayensis and Sphoeroides pachygaster; Egypt: first record of the Lessepsian fish Synchiropus sechellensis in the Egyptian Mediterranean waters.